2019
DOI: 10.3390/vibration2040020
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization-Based Framework for Nonlinear Model Selection and Identification

Abstract: This paper proposes an optimization-based framework to determine the type of nonlinear model present and identify its parameters. The objective in this optimization problem is to identify the parameters of a nonlinear model by minimizing the differences between the experimental and analytical responses at the measured coordinates of the nonlinear structure. The application of the method is demonstrated on a clamped beam subjected to a nonlinear electromagnetic force. In the proposed method, the assumption is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…To estimate and optimise the unknown parameters of the system, the optimisationbased framework is used by comparing the measured experimental data with the numerically simulated response of the system in the frequency domain. The objective function is defined to minimise the output error of the mathematical model of the system [23].…”
Section: The Optimisation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate and optimise the unknown parameters of the system, the optimisationbased framework is used by comparing the measured experimental data with the numerically simulated response of the system in the frequency domain. The objective function is defined to minimise the output error of the mathematical model of the system [23].…”
Section: The Optimisation Methodsmentioning
confidence: 99%
“…To acquire the dynamics of the nonlinear systems, the modified complex averaging technique (MCXA), finite element modelling (FEM), and arc-length continuation were utilised. A previously developed optimisation based framework (OBF) [23] was also employed on the cantilever beam, where the results were compared with those from the EDSM technique. It was found that the EDSM techniques were sensitive to any inaccuracies, but the resultant response may be employed as the initial parameter estimate for the OBF, lending to a more accurate representation of the response.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, an additional section (Section 5 -Identification Using Optimization) has been added to the paper. In this section, an optimization-based framework proposed by Taghipour et al [22] is used to identify the nonlinear force of the cantilever beam studied in the paper. The main objective of using this method is to eliminate the necessity for the usage of expansion method to estimate the response at the unmeasured coordinates.…”
Section: Replies To the Associate Editormentioning
confidence: 99%
“…The literature has an extensive range of identification approaches such as the force-state mapping technique, the restoring force surface method, the Hilbert transform, Bayesian system identification, Volterra series approximation, optimization-based identification approach, and the Equivalent Dynamic Stiffness Mapping technique [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Some methods assume the type of the nonlinearity is pre-known, and others do not rely on this assumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation